The air pollution picture in China. - Wang Yanjia
The authors describe how the fumes and floating dust trailing China's rapid economic growth have a concerned government legislating air-quality levels and running energy-reduction programs in the thermal power generation field
Keywords: China; Air pollution; Air-quality levels; Energy-reduction programmes; Floating dust; Fumes; Legislation; Rapid economic growth; Thermal power generation